198 Heart failure increases mitochondrial s-nitrosylation. (5th June 2017) - Radcliffe, Emma; Sun, Junhui; Aponte, Angel; Eisner, David; Murphy, Elizabeth; Trafford, Andrew
Abstract : Heart failure affects over 5 50 000 people living in the United Kingdom (1) and roughly half of those present with reduced cardiac ejection fraction (2). The electron transport chain (ETC) within the mitochondria is the principle source of ATP within cardiac muscle. Consequently, the regulation of the ETC in heart failure represents a potential rate limiting step to cardiac contraction in the disease state. The post-translational modification of proteins by nitric oxide, S-nitrosylation (S-NO) has previously been shown to have inhibitor effects on complex I activity (3). The aim of this study is therefore to investigate the role of S-NO and how this may regulate ETC activity in an ovine tachypaced model of heart failure. Tachypacing induced heart failure resulted in an increase in left ventricular diameter (3.100.06cm to 4.040.13cm, p<0.01, n=5), a thinning of the left ventricular free wall (8110mm to 263mm, p=0.01, n=5) and a reduction in left ventricular contractility (0.470.01 to 0.200.03, p<0.01, n=5). Mass spectrometry in combination with either tandem mass tags or S-NO resin assisted capture, was used to assess protein expression or S-NO abundance respectively. The total number of S-NO proteins identified increased from 23218 in control samples to 31428.3 in heart failure (p=0.02, n=6). Of those identified in both groups 79% showed an increase in S-NO abundance in heart failure. Mitochondrial content per unit of protein was unaltered in heart failure (p=0.93, n=5). However, S-NO of several ETC complex subunits was increased in the disease state (eg. NDUFS1 ↑ 2.9 fold, SDHA ↑ 1.2 fold, UQCRH ↑ 1.1 fold, n=6) in the absence of corresponding protein expression changes (eg. NDUFS1 ↓ 0.2 fold, SDHA ↓ 0.07 fold, UQCRH0.2 fold, n=5). In vitro S-NO of control mitochondria, using 0.2 mM S-nitrosoglutathione, oxidative phosphorylation by 52% (p<0.01, n=5). This study demonstrates that in heart failure there is a gross increase in the level of myocardial S-NO. Within the mitochondria, S-NO of electron transport chain proteins is also increased, having an inhibitory effect on ATP production. This work therefore provides a novel insight into how S-NO may contribute to the deterioration of cardiac contractile function in heart failure. References: . Townsend NWJ, Bhatnagar P, Wickramasinghe K, Rayner M. Cardiovascular disease statistics 2014. London: British Heart Foundation; 2014. Mozaffarian D, Benjamin EJ, Go AS, Arnett DK, Blaha MJ, Cushman M, et al. Executive Summary: Heart Disease and Stroke Statistics-2016 Update: A Report From the American Heart Association. Circulation. 2016;133(4):447-54. Epub 2016/01/27. . Chouchani ET, Methner C, Nadtochiy SM, Logan A, Pell VR, Ding SJ, et al. Cardioprotection by S-nitrosation of a cysteine switch on mitochondrial complex I. Nat Med. 2013;19(6):753.